The food-supplies of Essex Brent in the winter of 1960-61 - Burton, P J K (Wildfowl, 1962)
This short paper is a sequel to an account of surveys of Brent Goose Branta b. bernicla food supplies which appeared in last year's Report (Burton 1961).